Mediastinal Epidermoid Cyst in a 5-Year-Old Girl - Keren A. Sloan; Kokila Lakhoo (Georg Thieme Verlag KG, 2018)
A 5-year-old girl was referred to our unit with an incidental finding of a lesion on the right hemithorax situated within the right atrial shadow. Computed tomography thorax showed a well-defined soft tissue lesion felt to be consistent with a bronchogenic cyst. The lesion was located in the posterior mediastinum, adherent to the diaphragm and inferior vena cava, but did not extend within the wall of the esophagus. It was entirely excised via video-assisted thoracoscopy converted to open thoracotomy. Histopathology confirmed an encapsulated nodular tissue measuring 2.5 × 2.5 × 2 cm lined by squamous type epithelium. Chronic inflammatory cells and foreign body giant cell reaction were found in the cyst wall. The appearances were that of a benign epidermoid cyst.